2020
DOI: 10.1186/s40101-020-00240-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual variations and sex differences in hemodynamics with percutaneous arterial oxygen saturation (SpO2) in young Andean highlanders in Bolivia

Abstract: Background Many studies have reported specific adaptations to high altitude, but few studies have focused on physiological variations in high-altitude adaptation in Andean highlanders. This study aimed to investigate the relationships between SpO2 and related factors, including individual variations and sex differences, in Andean highlanders. Methods The participants were community-dwelling people in La Paz, Bolivia, aged 20 years and over (age range 20–34 years). A total of 50 men and 50 women participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…This proposal is consistent with the previous observation that male fetuses suffer more than female fetuses in an adverse maternal environment, and a higher expression of ADAM12 was detected in mothers who carry male fetuses in the mid-trimester than those carrying female fetuses, reflecting a sex-biased placental response, resulting in a higher prevalence of preeclampsia for male-carrying mothers (Myers et al 2015). In addition, for adults, there are sex differences in highaltitude adaptation (Murphy 2014;Nishimura et al 2020), which is in line with the proposed male-biased hypoxic response. Although the molecular mechanism remains unclear, a rat study found sex hormones could impact ventilator response to hypoxia during critical periods of respiratory development, and male rats show severer and more prevalent hypoxia response than female rats (Holley et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This proposal is consistent with the previous observation that male fetuses suffer more than female fetuses in an adverse maternal environment, and a higher expression of ADAM12 was detected in mothers who carry male fetuses in the mid-trimester than those carrying female fetuses, reflecting a sex-biased placental response, resulting in a higher prevalence of preeclampsia for male-carrying mothers (Myers et al 2015). In addition, for adults, there are sex differences in highaltitude adaptation (Murphy 2014;Nishimura et al 2020), which is in line with the proposed male-biased hypoxic response. Although the molecular mechanism remains unclear, a rat study found sex hormones could impact ventilator response to hypoxia during critical periods of respiratory development, and male rats show severer and more prevalent hypoxia response than female rats (Holley et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously reported sex and individual differences in hemodynamics and SpO 2 in young Andean highlanders in Bolivia (altitude, 3700–4000 m) in a study of a similar duration, using the same protocol [ 14 ]. SpO 2 was higher in the present study (mean [95 % CI ], 92.4% [92.0–92.8%]) compared with the Andean highlanders (91% [90.0–91.0%]).…”
Section: Discussionmentioning
confidence: 99%
“…Although populational differences have been well discussed, there is limited knowledge of physiological variations in highlanders [ 3 , 10 ]. From the perspective of physiological anthropology, various studies have conducted field research to investigate variation in physiological response from the perspective of acute hypobaric hypoxia in lowlanders [ 11 , 12 ] or of physiological variation in highlanders [ 6 , 13 , 14 ]. In our previous field research, we investigated the health status of Tibetans in Tsarang village (altitude, 3570 m) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study subjects had no documented clinical problems such as cardiovascular and respiratory diseases. Of note, these subjects were also recruited in our previous studies on toothache experience and physiological traits [40,41].…”
Section: Study Subjectsmentioning
confidence: 99%